To Re-Explore the Causality between Barriers to Renewable Energy Development: A Case Study of Wind Energy - Yen-Ching Lin; Shih-Chieh Huang; Shang-Lien Lo (Energies, 2013)
The development of wind energy in developing countries has its limitations. This study adapted quantitative approaches to explore the causality relationships among these barriers. It was found that different areas of obstacles did affect one another; by barrier inference we learned that a lack of national policy caused other disorders, and that the occurrence of these disorders eventually resulted either directly or indirectly in high investment costs. Thus, the question of how to effectively reduce the investment cost of wind energy development is the most important issue to developing countries. Furthermore, the results of this study clarified that wind intermittency would not be the main reason hindering short and mid-term wind power development. However, from a long-term perspective, the impact of intermittency still cannot be treated lightly, as it was found that for each standard deviation unit improvement of the intermittency, the investment cost-effectiveness improvement increased by 0.185 σ, which was 1.78 times higher than the impact from national policies. Therefore, aside from strengthening the national policies in establishing a suitable institutional framework, we recommend that policy-makers should also emphasize the establishment of an economic assessment of available sites, a detailed wind resource assessment and improved forecasting of technical applications.